Women sentenced to jail in New York City - Brennan, Pauline Katherine (Criminal justice recent scholarship, 2002)
Race/ethnicity, social class, and gender -- Theoretical discussions of female-defendant -- Empirical examinations of female-defendant -- Propositions and research question -- Data and methodology -- General models -- Race/ethnicity-specific models -- Offense-specific models -- Summary and discussion.